2020
DOI: 10.15517/ijds.2021.43538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light Sources on Bond Strength of Different Composite Resins Repaired with Bulk-Fill Composite

Abstract: The aim of this study was to evaluate and compare the effects of different light sources on shear bond strength when bulk-fill composite was used for the repair of different composite resins. A total of 126 samples made from six resin composites with different properties were aged (thermal-cycling with 5000 cycle), exposed to the same surface treatments and adhesive procedure. Then, they were repaired with a bulk-fill composite. At the polymerization step, each group was divided into three subgroups (n=7) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Moreover, this device has a wavelength of only one profile, and knowing that Filtek One Bulk Fill contains camphorquinone as the only photoinitiator, it would allow the total absorption of the light, favouring the bond strength. The presence of zirconia/silica also improved the mechanical properties of Filtek One Bulk Fill, which is supported by the results obtained by Kiliç et al 44 …”
Section: Discussionsupporting
confidence: 85%
“…Moreover, this device has a wavelength of only one profile, and knowing that Filtek One Bulk Fill contains camphorquinone as the only photoinitiator, it would allow the total absorption of the light, favouring the bond strength. The presence of zirconia/silica also improved the mechanical properties of Filtek One Bulk Fill, which is supported by the results obtained by Kiliç et al 44 …”
Section: Discussionsupporting
confidence: 85%
“…26 In another study investigating the effect of LCUs on the bonding strength in the repair of different composites with bulk-fill composites, the Elipar DeepCure-S provided better bonding strength than the Valo light device, and this was attributed to the Elipar DeepCure-S light device providing better polymerization at the bottom of the composite. 27 All light curing units used in the study has provided significantly high polymerization depths at 40 second compared to 10 and 20 seconds (p<0.05). This can be explained by prolonged curing times allow the formation of additional cross-links in higher depths of restorative material and lead to a more homogeneous polymer network.…”
Section: Discussionmentioning
confidence: 83%
“…36 The data of this study are in agreement with those of previous studies. 9,36,56,58 However, it has also been reported that the composite bond strength decreases after performing a higher number of thermal cycles. 59 Present study established a statistically significant decrease in the repair shear bond strength values after thermal cycling only in the chlorhexidine group (Table 1).…”
Section: Discussionmentioning
confidence: 99%